ADOPSI TEKNOLOGI DALAM PENINGKATAN PENJUALAN UMKM BERKAH DY PADA MASA PANDEMI COVID-19 - Rike Tri Kumala Dewi; Carissa Velda; Dan Stefani Harminto; Diaz Adrian Putra; Fiona Carissa; Matthew Nathanael; Nadya Carolina; Melinda Kathleen; Tristan Aji Ibrahim (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
The COVID-19 pandemic gives a big impact on the economy of Small and Medium-Sized Enterprises (SMEs), one of them is Berkah DY which is located in the sub-district of Cijoho, Kuningan Regency, West Java. With the Community Development project organized by Universitas Prasetiya Mulya, it was hoped that it can increase the market sales of Berkah DY during the pandemic. The used method is education and training about the adoption of technology in three aspects, i.e marketing, operational, and finance. The target of this activity was to maximize the efficiency of online marketing through e-commerce; produce a product that has a long shelf life; do financial records rapidly, accurately, and automatically. The results of this activity showed that there was an overall increase in market sales of 163,94%. With this program, the partner has the knowledge and insights about the benefits of technology in doing business during the COVID-19 pandemic.